Fish Cultivation Engineering in Buckets Based On the Internet of Things (IoT) - Dodi Yudo Setyawan; Ari Widiantoko; Agustina Cindy Amelia; Lia Rosmalia; Melia Gripin Setiawati; Novi Herawadi Sudibyo (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The development and population growth that are increasing from time to time have an impact on the expansion of housing areas. This results in a decrease in the land that can be used by the community for raising livestock and planting crops. To keep maximizing the remaining land, several community groups utilize the remaining land by cultivating fish through the Fish Cultivation Technique in Buckets. The current problem is that fish cultivators are still manually measuring water quality by visiting fish ponds and using simple measuring instruments. It affects the effectiveness of fish farming. so the researchers create a monitoring system with the title Fish Cultivation Technique in Bucket Based on the Internet Of Things (IoT). In this study, researchers used 3 sensors: the DS18B20 sensor, the Turbidity sensor, and the water level sensor. The DS18B20 sensor is used to measure the water temperature, the turbidity sensor is used to measure the turbidity of the water, and the water level sensor is used to measure the water level. From the test results of the whole system, it can be seen that if the water turbidity sensor reading is less than 15.24 NTU then the bucket water is said to be normal, while if the sensor reading is more than 15.24 NTU, the water is said to be cloudy so the relay will be on to drain the bucket water. While the results of the water temperature sensor readings are less than 26.2 to 30.0oC then the water is said to be normal bucket water. If the temperature sensor readings are more than 30oC then the water is said to be hot the relay will be active to turn on the aeration. Keywords—Fish, Turbidity, DS18B20, Water Level, Internet of Things